The Effect of Fingerprint Attendance Effectiveness on Compensation with Discipline as a Mediating Variable at PT. XYZ - Varadilla Arkadewi; Nur Cahyadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to evaluate the effectiveness of the fingerprint attendance system on compensation, with discipline as a mediating variable. The study was conducted at PT. XYZ, involving a sample of 110 employees from a population of 689 people. Data collection was carried out through a questionnaire with a Likert scale, then analyzed using the PLS-SEM method with SmartPLS 4 software. The analysis process includes validity, reliability, hypothesis testing, and model fit tests. The results of the study indicate that the fingerprint attendance system significantly improves employee discipline, which then has a positive impact on compensation. In addition, fingerprint attendance also has a direct effect on compensation. Discipline has been shown to be an important mediator in building a disciplined work culture, increasing transparency in working time management, and ensuring fair and productive compensation. This study highlights the important role of technology in human resource management, especially in creating an efficient, transparent, and productivity-supporting work system. These findings provide important insights for companies in designing effective technology-based discipline and compensation policies.